The Relationship Between Excellent Midwifery Services With The Level Of Kb Acceptors Satisfaction In Public Health Center Hamparan Perak Deli Serdang District Year 2019 - Manurung, Herna Rinayanti (Mitra Husada Health Internasional Conference (MIHHICo), 2023)
Excellent service or service excellence is a form of necessity or based on the results of a survey that was taken for 3 consecutive years, right in January - May 2017, there were 72 family planning receptors who came to the Hamparan Perak Puskesmas, in 2018 as many as 97 people, and years 2019, the number of kb acceptors regarding the coverage of midwifery who came at the Hamparan Perak Health Center was 110 people. Respondents were compiled by using proportional random sampling, that is, sampling of members of the population was carried out randomly without considering the strata in the population. From the results of the research, entitled Relationship of Excellent Service Midwifery Services with the Satisfaction Level of Family Planning Receptors at the Hamparan Perak Public Health Center, Deli Serdang Regency in 2019, there were 86 people. From the results of the study, it can be seen that based on the excellent service midwifery service taken from 86 respondents, the majority were in the good category as many as 65 people (75.6%), the poor category was 8 people (9.3%), the moderate category was 13 people (15, 1%). There is a significant relationship between service excellence relationship with the level of patient satisfaction at the Hamparan Perak Community Health Center by looking at the Asymp value. Sig (2-sided) = 0.009 less than 0.05. There is a relationship between service excellent midwifery service on the satisfaction of kb acceptors.